Pengaruh Perputaran Kas, Perputaran Persediaan, dan Perputaran Piutang Terhadap Return On Assets (ROA) pada PT. Indofood Sukses Makmur Tbk Periode 2008-2015 - Dona Elvia Desi (Universitas Batanghari Jambi, 2018)
This research aims to know the influence between the cash turnover, inventory turnover, and turnover accounts receivable against the Return on Asset (ROA) either partially or simultaneously on a PT Indofood 2008-2015 Makmur Tbk period of Success and to knowing the magnitude of influence between the cash turnover, inventory turnover, and turnover accounts receivable against the Return on Asset (ROA) either partially or simultaneously on a PT Indofood 2008-2015 Makmur Tbk Successful period. With linear regression equation enggumakan, double and test hypotheses as well as the determinant of the coefficient of t and F test then obtained simultaneous results that there is significant influence between the cash turnover, inventory turnover and accounts receivable turnover against the Return On Assets (ROA) on PT Indofood 2008-2015 Makmur Tbk Success period, this is evidenced by the value count > F table F and significant > 0.05. Partially, there is no significant influence between the cash turnover against the Return On Assets (ROA) on PT Indofood 2008-2015 Makmur Tbk Success period, there were no significant effects between inventory turnover against the Return On Assets ( ROA) on PT Indofood 2008-2015 Makmur Tbk Successful period and there were no significant effects between turnaround receivable against the Return On Assets (ROA) on PT Indofood Successful Prosperous Tbk period 2008-this 2015hal evidenced by each value t calculate < t table and significance > 0.05. Keywords: turnover turnover cash, inventory, accounts receivable turnover, ROA